the difficulties of personal and professional scientific research among higher education teachers - A f - jellab, mosbah (Journal of Social Sciences and Humanities, 2022)
The difficulties of scientific research are generally reflected in those research obstacles that we can study from three aspects. The first includes obstacles related to research. The second includes obstacles related to the researcher. The third includes obstacles related to the environment and nature of work. The objective The study is to know the difficulties of personal and professional scientific research, among teachers of higher education at the Algerian University. The study also aimed to reveal the sub-goals that the study dealt with in detail, through indicators that measure the degree of personal and professional difficulties, and the measurement of the existence of differences among teachers in the specialty variable, as well as the measurement of the existence of differences in the difficulties of scientific research. Personal and professional by gender, scientific rank and experience. We followed the descriptive approach and a questionnaire of (33) items Prepared by the researcher, is characterized by validity and Reliability, on a sample of 33 teach at the University of M'sila, we used SPSS, and the appropriate statistical methods. The study achieved the following results: - The teachers suffer from high personal and professional difficulties. - There are statistically significant differences at the 0.01 level between professors in the difficulties of personal scientific research due to the specialty variable for the humanities and social sciences. - There were no statistically significant differences in personal and professional difficulties in scientific research, by sex, grade and years of professional experience